The Effect Of Fiscal Decentralization On The Open Unemployment Rate In The Province Of DIY - Iqbal (Jurnal Ekonomi Pembangunan, 2023)
This study aims to find empirical evidence on the effect of general allocation funds, special allocation funds, production sharing funds, and spending on goods and services on the open unemployment rate. The data used in this study is panel data, a combination of time series data (2012-2020), and cross-sectional data (5 regencies/cities in the Special Province of Yogyakarta). The results show that the Special Allocation Fund and Revenue Sharing Fund significantly positively affected the Open Unemployment Rate in the Special Region of Yogyakarta Province from 2012-2020.